Enhanced growth and yield in semi-indeterminate tomato (Solanum lycopersicum): A heterosis study under protected condition - K R, NAYANA; V, SRINIVASA; DEVARAJU,; K A, SHRILATHA (The Indian Journal of Agricultural Sciences, 2024)
A diallel design was employed to assess the magnitude of heterosis, aiming to improve growth and yield of semi- indeterminate tomato by identifying the desirable cross- combinations. Five semi-indeterminate tomato genotypes (VRT13, EC15127, EC362941, EC521061 and EC521069) were crossed in diallel mating fashion during rainy (kharif) season of 2020. Crosses and the parents were examined for heterosis studies under naturally ventilated polyhouse during winter (rabi) season of 2020–21. The results revealed the presence of heterotic vigour in the growth and yield characteristics of the hybrids with significant differences among the traits studied. Hybrids from crosses EC15127 × EC362941 and VRT13 × EC362941 resulted negative heterosis over mid and better parent, respectively for days to first flowering indicating their earliness for flowering. VRT13 × EC15127 and EC15127 × EC362941 noticed heterosis over better and mid parent, respectively for fruit yield. Based on overall performance, the cross combinations EC15127 × EC362941, VRT13 × EC521061, VRT13 × EC15127, VRT13 × EC362941 and EC521069 × EC362941 were performed best over their parents for growth and yield parameters. Hence, these hybrids can be exploited directly or can be used further for development of improved commercial lines